2022
DOI: 10.1002/uar2.20022
|View full text |Cite
|
Sign up to set email alerts
|

Leaf mold compost reduces waste, improves soil and microbial properties, and increases tomato productivity

Abstract: Soils in urban settings are often degraded, which can prevent growers from optimizing the health and productivity of their crops. In this study, we investigated whether amending soil with a locally made leaf-mold compost could (a) improve soil chemical and biological properties, (b) increase survival of a microbial inoculant with plant growth promoting and disease suppressive capabilities, and (c) enhance the yield and quality of a tomato crop. Results were promising, with dramatically greater concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…( Liu et al, 2019 ; Sun et al, 2021 ), and Chaetomiaceae ( Castelan-Sanchez et al, 2019 ), have all been reported to tolerate salinity stress and have potential PGP activities. Since Sistotrema and Trichosporon were also positively correlated with SOM in the present study, future studies should consider investigating whether methods that can increase SOM, such as growing cover crops or amending soils with composts ( Hoagland et al, 2008 ; Rudisill et al, 2015 ; Reeve et al, 2016 ; Richardville et al, 2022 ), can enhance their populations in these soils.…”
Section: Discussionmentioning
confidence: 72%
“…( Liu et al, 2019 ; Sun et al, 2021 ), and Chaetomiaceae ( Castelan-Sanchez et al, 2019 ), have all been reported to tolerate salinity stress and have potential PGP activities. Since Sistotrema and Trichosporon were also positively correlated with SOM in the present study, future studies should consider investigating whether methods that can increase SOM, such as growing cover crops or amending soils with composts ( Hoagland et al, 2008 ; Rudisill et al, 2015 ; Reeve et al, 2016 ; Richardville et al, 2022 ), can enhance their populations in these soils.…”
Section: Discussionmentioning
confidence: 72%
“…Leaf compost and mixed compost contain lower nutrients but have sufficient soil organic matter (SOM), hence improving soil health ( Choudhary et al., 2020 ). Further, the SOM increases the water-holding capacity of the soils and also makes more nutrients available to the plants ( Richardville et al., 2022 ). It can be inferred from the results that as LC acts as more of a soil conditioner, soil retains externally applied inorganic nutrients more efficiently and improves nutrient availability to plants ( Bhupenchandra et al., 2022b ; Gupta et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%